Thinking the family: institutionalism versus globalism. Theoretical clarity, strange developments & huge problems - Wladika, Michael (Forum Teologiczne, 2022)
This text intends to show: First: There is no theoretical unclarity surrounding the notion of the family. Taken together, its spelling-out in Aristotle and St. Augustine is, as it were: perfect, intellectually completely satisfying. One could even go so far as to say that this is a truth universally acknowledged among those who know what they are talking about. This is recapitulated with a special stress on theoretical stringency. But then: There seem to be many cultured despisers of the family. The force of the zeitgeist runs strong here, and it will not simply go away. Strange developments lead to and huge problems surround and result from social atomism, anti-institutionalistic and globalistic concepts. This is developed ex negativo, against the background of robust institutionalism. Jürgen Habermas` destructive universalism e.g. can be understood via concentration on Arnold Gehlen`s institution-theory. The text tries to lead to insight into this syllogism: Man is institutionalistic by nature. Globalism or internationalism is intrinsically anti-institutionalistic. Globalism or internationalism therefore directly leads to the abolition of man. But, finally: Of course all this can be overcome. The way to transcend the zeitgeist-tendencies is the only necessary institution, the family. The family liberates practically, and it clarifies theoretically.